County-Level Characteristics Associated with Variation in ESKD Mortality in the United States, 2010–2018. Issue 5 (26th May 2022) - Snow, Kylie K.; Patzer, Rachel E.; Patel, Shivani A.; Harding, Jessica L.
Key Points: There is substantial variation in county-level ESKD mortality across the United States, with highest rates seen in the Southeastern United States. County characteristics explain approximately 19% of variation in ESKD mortality. Counties with high ESKD-related mortality may benefit from targeted and multilevel interventions. Visual Abstract: Abstract : Background: Geographic and neighborhood-level factors, such as poverty and education, have been associated with an increased risk for incident ESKD, likelihood of receiving pre-ESKD care, and likelihood of receiving a transplant. However, few studies have examined whether these same factors are associated with ESKD mortality. In this study, we examined county-level variation in ESKD mortality and identified county-level characteristics associated with this variation. Methods: We identified 1, 515, 986 individuals (aged 18–84 years) initiating RRT (dialysis or transplant) between 2010 and 2018 using the United States Renal Data System. Among 2781 counties, we estimated county-level, all-cause, age-standardized mortality rates (ASMR) among patients with ESKD. We then identified county-level demographic ( e.g., percent female), socioeconomic ( e.g., percent unemployed), healthcare ( e.g., percent without health insurance), and health behavior ( e.g., percent current smokers) characteristics associated with ASMR using multivariable hierarchic linear mixed models and quantified the percentage of ASMR variation explained by county-level characteristics. Results: County-level ESKD ASMR ranged from 45 to 1022 per 1000 person-years (PY) (mean, 119 per 1000 PY). ASMRs were highest in counties located in the Tennessee Valley and Appalachia regions, and lowest in counties located in New England, the Pacific Northwest, and Southern California. In fully adjusted models, county-level characteristics significantly associated with higher ESKD mortality included a lower percentage of Black residents (−4.94 per 1000 PY), lower transplant rate (−4.08 per 1000 PY), and higher healthcare expenditures (5.21 per 1000 PY). Overall, county-level characteristics explained 19% of variation in ESKD mortality. Conclusions: Counties with high ESKD-related mortality may benefit from targeted and multilevel interventions that combine knowledge from a growing evidence base on the interplay between individual and community-level factors associated with ESKD mortality.